Effect of mare’s milk prebiotic supplementation on the gut microbiome and the immune system following antibiotic therapy - Madiyar Nurgaziyev; YERMEK AITENOV; ZHANAGUL KHASSENBEKOVA; SANIYA AKPANOVA; KAIRAT RYSBEKOV; SAMAT KOZHAKHMETOV; AYAULYM NURGOZHINA; SHYNGGYS SERGAZY; LAURA CHULENBAYEVA; ZHANNA OSPANOVA; ALTYNAI TUYAKOVA; NURISLAM MUKHAMBETGANOV; RASHIDA SATTYBAYEVA; SALTANAT URAZOVA; NAZYM GALYMGOZHINA; ANARA ZHUMADILOVA; ALEXANDR GULYAEV; ALMAGUL KUSHUGULOVA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nurgaziyev M, Atenov Y, Khassenbekova Z, Akpanova S, Rysbekov K, Kozhakhmetov S, Nurgozhina A, Sergazy S, Chulenbayeva L, Ospanova Z, Tuyakova A, Mukhambetganov N, Sattybayeva R, Urazova S, Galymgozhina N, Zhumadilova A, Gulyaev A, Kushugulova A. 2020. Effect of mare’s milk prebiotic supplementation on the gut microbiome and the immune system following antibiotic therapy. Biodiversitas 21: 5065-5071. Antibiotic treatment can severely affect the gut microbiome for short-term and long-term consequences. Probiotic and prebiotic supplements are widely prescribed to modulate the composition and function of the human gut microbiome. The current study aims to determine the impacts of mare’s milk prebiotics on the diversity of gut bacterial communities and the local immune system when administered during and after a course of antibiotic therapy. Six children aged 4 to 5 years diagnosed with bilateral bronchopneumonia were prescribed cephalosporin (cefuroxime) antibiotics. During the 60 days of the study, three children consumed mare’s milk prebiotics, while the other three did not. Fecal samples were collected daily during antibiotic therapy and every five days after the last day of antibiotic treatment. Total DNA was isolated, and the taxonomic composition of the gut microbiome was analyzed by sequencing the 16S rRNA gene (V1-V3 region). The MULTIPLEX MAP platform was used to evaluate the local immune status. The relative abundance of 11 genera was reduced and did not recover until the last day of the study. The abundance of Bacteroides was not significantly altered in either group. Christensenella, Rothia, Abiotrophia, Acinetobacter, Anaerotruncus, Holdemania, and Turicibacter numbers were significantly increased on day five and remained at the same level during the study period. Cephalosporin administration also reduced the levels of pro-inflammatory and anti-inflammatory cytokines/chemokines (MIP1?, TNF?, GMCSF, GCSF, sCD40L, FGF2, TGF?, IL1?, and IP10).